Effect of compaction force on the mechanical properties of novel mixtures of naturally derived hydroxyapatite ceramics - Obinna Anayo Osuchukwu; Emeka Obiora Anisiji; Precious Osayamen Etinosa; Ibitoye Opeyemi Isaac; Peter Gbenga Oni; Victor D. Aderibigbe; Kazeem O. Rabiu; Oladele O. Arogundade; Oreoluwa Oginni; David Olubiyi Obada (Results in Materials)
The applications of hydroxyapatite (HAp) with remarkable chemical and physico-mechanical properties are important in biomedical engineering. This research studied the effect of compaction force (5,10, and 15 kN) on the crystallographic, physical, and mechanical, properties of ceramics produced from novel mixtures of non-separated animal bones and catfish derived HAp prepared through a sol-gel technique at temperatures of 1050 and 1150°C. The sintering temperatures (1050 and 1150°C) were used to process the powders for 2 h at the heating rate of 5°C/min. The nomenclature of the samples was such that the corresponding temperatures assigned were sometimes ascribed such as B100-1050°C, C100-1050°C, B100-1150°C, C100-1150°C, etc., and in some cases for simplicity, samples with the suffix A referred to variants sintered at 1050°C, while samples with the suffix B referred to variants sintered at 1150°C.The obtained porosities for the samples ranged from 38.22 % (B75/C25-1150°C) to 49.81 % (B100-1050°C). At 1050°C, the highest microhardness recorded for 5 kN was 0.48 GPa (B25/C75), for 10 kN was 0.48 GPa (B25/C75), and for 15 kN was 0.56 GPa (B50/C50). At 1150°C, the highest microhardness recorded for 5 kN was 1.00 GPa (B75/C25), for 10 kN was 0.93 GPa (B100), and for 15 kN was 0.92 GPa (B100). The compressive strengths of sample B100 were the highest at every point of measurement. From the results obtained, a compaction force of 5 kN is recommended to produce bioceramics with suitable physical and mechanical properties for biomedical applications.